A cross-sectional epidemiological study of socio-demographic characteristics, and the functional assessment in geriatric population in field practice area of an urban health centre - Sandeep Mishra; Kinge, Amol; Ashwini Umesh Patekar; Shreekanth Krishnaiah Jakkula (Asian Journal of Medical Sciences, 2023)
Background: India like many other developing countries in the world is witnessing the rapid aging of its population. Urbanization, modernization, and globalization have led to change in the economic structure, the erosion of societal values, weakening of social values, and social institutions such as the joint family. Active aging aims to extend healthy life expectancy and quality of life (QOL) in older persons, and the QOL are largely determined by its ability to maintain autonomy and independence. Aims and Objectives: The present study was conducted at a teriary apex institute to study the socio-demographic characteristics, and the functional assessment in the elderly subjects in urban community. Materials and Methods: It was a cross-sectional observational study conducted at the area situated near western suburb of metro city and population of around one lakh sixty thousand. It consisted of housing buildings, multiple slum area. The current study was conducted over 1 year 6 months (18 months).The sampling unit being 102 Geriatric individuals of selected area of urban health center. Results: Out of 102 study, subjects 22 (21.56%) were complete independent to perform daily instrumental activities. Maximum study 48 (47.05%) subjects were required moderate assistance for performing the instrumental activities. Numbers of female study subjects were more among moderates assistance 24 (44.44%) and modified assistance 20 (19.60%). Out of 102 study subjects 55 (53.92%) were complete independent followed by 30 (29.41%) modified independence. Numbers of female subjects were more among moderate assistance 10 (58.82%). Conclusion: No study subject was dependent or maximal assistance for their self-care activities. Male and female in the present study can perform their self-care activities of daily living with equal efficiency.